2020
DOI: 10.1016/j.ijid.2020.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different samples for 2019 novel coronavirus detection by nucleic acid amplification tests

Abstract: A severe respiratory ongoing outbreak of pneumonia associated with 2019 novel coronavirus was recently emerged in China. Here, we reported the epidemiological, clinical, laboratory and radiological characteristics of 19 suspect cases. We compared J o u r n a l P r e -p r o o f

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
339
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(355 citation statements)
references
References 10 publications
9
339
0
7
Order By: Relevance
“…In this model, the probability of RT-PCR assays to detect one copy of SARS-CoV-2 is only 26%. This finding may explain, at least in part, the low reported 47-56% detection rates of SARS-CoV-2 in positive samples by RT-PCR 17,22 . We further found that the LOD appears to be independent of the virus genome size.…”
Section: Mathematical Model Of Rt-pcrmentioning
confidence: 94%
See 2 more Smart Citations
“…In this model, the probability of RT-PCR assays to detect one copy of SARS-CoV-2 is only 26%. This finding may explain, at least in part, the low reported 47-56% detection rates of SARS-CoV-2 in positive samples by RT-PCR 17,22 . We further found that the LOD appears to be independent of the virus genome size.…”
Section: Mathematical Model Of Rt-pcrmentioning
confidence: 94%
“…Currently, RT-PCR is considered the gold standard of diagnosis for SARS-CoV-2 due to its ease of use and high sensitivity. RT-PCR has been reported to detect SARS-CoV-2 in saliva 15 , pharyngeal swab, blood, anal swab 16 , urine, stool 17 , and sputum specimens 18 . In laboratory conditions, the RT-PCR methodology has been shown to detect 4-8 copies of virus, through amplification of targets in the Orf1ab, E and N viral genes, at 95% confidence intervals [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anorexia, Chills, Shortness of breath, dyspnea, chest pain, confusion, and nausea/vomiting were reported in respectively 5, 5, 6, 5, 7, 2, and 9 studies. Overall prevalence of these symptoms was 24% (95% CI, 13-34), 19% (95% CI, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], 27% (95% CI, 12-42), 31% (95% CI, 14-48), 6% (95% CI, 2-9), 1% (95% CI, 0-2) and 6% (95% CI, 3-8) (Supplementary File and Table 2).…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Diese ist bei medizinischen Maßnahmen und Operationen im Nasen-Rachen-Raum und Kopf-Hals-Bereich besonders hoch. Erste Studien deuten auf einen niedrigen oder ausbleibenden Nachweis von SARS-CoV-2 im Urin und Blut von an COVID-19 erkrankten Patienten hin, wohingegen das Virus im Stuhl hochfrequent nachweisbar war [8,9]. Weiterhin sollte auch ein besonderes Augenmerk auf laparoskopischen Eingriffen liegen, für die Studien eine Virusdissemination durch das Pneumoperitoneum beschrieben haben [10,11].…”
Section: Interventionen Und Operationen An Sars-cov-2-positiven Patieunclassified